Effects of Different TiO2 Solution Compositions on Efficiency of Quantum Dot Solar Cell (QDSC) by Sol-Gel Method - Farooq, W. A.; Soylu, M.; Amanullah, F. M.; Yahia, I. S.; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
Quantum dot sensitized solar cells (QDSC) based on TiO2-coated CdS prepared by a successive ionic layer adsorption and reaction (SILAR) method were fabricated. The calcualted photovoltaic parameters were evaluated in terms of average macroscopic ratios of the mixed solvents. An optimum volume ratios of H2O in TiO2 at volume ratios (TTIP:EtOH:H2O:HCl) are 1:15:30:0.2, 1:15:60:0.2 and 1:15:120:0.2, respectively which could strongly affect the performance of the solar cells. The efficiency of the CdS/TiO2 solar cells containing an average volume ratio of H2O in TiO2 was higher than that of those in solar cells containing high volume ratio. So. TiO2 with volume ration (TTIP:EtOH:H2O:HCl of 1:15:60:0.2) have shown the highest photovoltaic conversion efficiency of 2.30% as the working photoelectrode of a QD-sensitized solar cell. TiO2 by sol-gel method in relevant solution composition with QD-CdS have been shown to be a promising candidate for efficient light harvesting devices. Our work is a primary results on the filed of CdS/TiO2 based QDSC.
Keywords: TiO2; CdS; Solution; Solar Cells